Highly Stereoselective C‐Glycosylation by Photocatalytic Decarboxylative Alkynylation on Anomeric Position: A Facile Access to Alkynyl C‐Glycosides. Issue 6 (13th January 2022) - Lu, KaiLin; Ma, Yingying; Liu, Shihui; Guo, Shixun; Zhang, Yongqiang
Comprehensive Summary: The highly stereoselective synthesis of diverse medicinally valuable alkynyl C ‐glycosides under mild and green reaction conditions remains a great challenge. Herein, we wish to report a visible‐light induced photocatalytic decarboxylative alkynylation approach. By utilizing an iridium photocatalyst in the presence of visible light, glycosyl radicals are in‐situ generated via the decarboxylation of anomeric acids and efficiently coupled with a variety of ethynylbenziodoxolones (EBXs), which allows the facile synthesis of a variety of alkynyl C ‐glycosides in moderate to high yields and with excellent diastereoselectivity. Abstract : A visible‐light induced photocatalytic decarboxylative alkynylation approach has been developed for the synthesis of a variety of medicinally valuable alkynyl C ‐glycosides.